The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jmedchem.1c02045
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of TNP-2198, a Dual-Targeted Rifamycin-Nitroimidazole Conjugate with Potent Activity against Microaerophilic and Anaerobic Bacterial Pathogens

Abstract: TNP-2198, a stable conjugate of a rifamycin pharmacophore and a nitroimidazole pharmacophore, has been designed, synthesized, and evaluated as a novel dual-targeted antibacterial agent for the treatment of microaerophilic and anaerobic bacterial infections. TNP-2198 exhibits greater activity than a 1:1 molar mixture of the parent drugs and exhibits activity against strains resistant to both rifamycins and nitroimidazoles. A crystal structure of TNP-2198 bound to a Mycobacterium tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Besides the exploration of compounds acting on novel antibiotic targets, one avenue is to expand the utility of already existing pharmacologic motifs, such as nitroimidazoles. Ma et al recently reported about the potent dual-targeting rifamycin–nitroimidazole conjugate TNP-2198 exploiting polypharmacology against microaerophilic and anaerobic bacteria . Furthermore, the recently reported nitroimidazole indolin-2-one hybrids were shown to expand the potency of nitroimidazoles, which were classically restricted to the treatment of anaerobic bacteria, to aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the exploration of compounds acting on novel antibiotic targets, one avenue is to expand the utility of already existing pharmacologic motifs, such as nitroimidazoles. Ma et al recently reported about the potent dual-targeting rifamycin–nitroimidazole conjugate TNP-2198 exploiting polypharmacology against microaerophilic and anaerobic bacteria . Furthermore, the recently reported nitroimidazole indolin-2-one hybrids were shown to expand the potency of nitroimidazoles, which were classically restricted to the treatment of anaerobic bacteria, to aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al recently reported about the potent dual-targeting rifamycin–nitroimidazole conjugate TNP-2198 exploiting polypharmacology against microaerophilic and anaerobic bacteria. 25 Furthermore, the recently reported nitroimidazole indolin-2-one hybrids were shown to expand the potency of nitroimidazoles, which were classically restricted to the treatment of anaerobic bacteria, to aerobic conditions. Here, we unravel an unexpected putative dual MoA of nitroimidazole indolin-2-one hybrids in pathogenic S. aureus that is potentially responsible for this gain of aerobic activity.…”
Section: Discussionmentioning
confidence: 99%
“… ,, Initially, the silver salt AgSbF 6 reacted with [Cp*RhCl 2 ] 2 to form a cationic rhodium complex A . K 2 CO 3 -assisted concerted metalation deprotonation leads to the coordination of the nitrogen atom of the amide/sulfoximine substrate B with catalytically active rhodium species A , generating a five-membered Rh­(III)-intermediate C through a reversible C­(sp)-H activation reaction. Subsequently, a seven-membered rhodium metallacycle intermediate D was afforded when rhodacycle C underwent an olefin insertion with methyl 2-chloroacrylate 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen-containing heterocycles are key structural motifs in organic chemistry since numerous natural products, polymeric materials, and drugs feature these skeletons (Figure ). Tremendous efforts have been dedicated to the construction of nitrogen-containing heterocycles, resulting in C–N bond formation and C–N annulation reactions gaining significant attraction.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Previous studies on the advancement of DprE1 inhibitors proposed that high throughput screening, molecular modeling, docking, functional genomics, and proteomics are all significant in identifying novel chemical scaffolds as potential TB chemotherapy molecules. 20,25 Using the PubChem and ZINC databases, we used insilicobased virtual screening to find potential chemical compounds that can serve as DprE1 inhibitors. In the present study, a library of 100 molecules with a structural resemblance to bedaquiline (FDA approved anti-TB drug) was generated to identify novel and promising agents against the DprE1, a vulnerable drug target in Mtb.…”
Section: Introductionmentioning
confidence: 99%